EXAMINING THE FACTORS INFLUENCING THE INTENTION TO BUY AN ELECTRIC VEHICLE - Saleh, Hendra Noor; Maupa, Haris; Sadat, Andi Muhammad (Graduate Program of Universitas Tarumanagara, 2024)
Even though electric vehicles have been introduced for a long time, demand for electric vehicles still needs to be improved. Therefore, research on consumer adoption of electric vehicles needs to be carried out to fill the existing research gaps. This research examines the relationship between Perceived usefulness, Perceived ease of use, and Customers' experience on Intention to buy an electric vehicle. A total of 269 respondents who live in DKI Jakarta were collected through an online survey using a purposive sampling technique. Data processing was carried out using a PLS-SEM approach using Smart PLS3 software. The results show that all of the five proposed hypotheses are significant. This means that Perceived usefulness, Perceived ease of use, and Customers' experience are essential variables that can significantly influence customers' Intention to buy an electric vehicle. This research contributes to providing information for companies and regulators regarding understanding consumer behavior in purchasing electric vehicles.